2007
DOI: 10.1186/1475-2875-6-29
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate – amodiaquine combination therapy for falciparum malaria in young Gabonese children

Abstract: BackgroundArtesunate-amodiaquine combination for the treatment of childhood malaria is one of the artemisinin combination therapies (ACTs) recommended by National authorities in many African countries today. Effectiveness data on this combination in young children is scarce.MethodsThe effectiveness of three daily doses of artesunate plus amodiaquine combination given unsupervised (n = 32), compared with the efficacy when given under full supervision (n = 29) to children with falciparum malaria were assessed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 24 publications
6
23
1
1
Order By: Relevance
“…In the Democratic Republic of Congo, two studies conducted between 2003 and 2004 in Equator, South Kivu, and Katanga provinces reported paradoxical results with 85%, 93%, and 100% of ACPR, respectively [33,34]. In two studies conducted in Gabon, AS + AQ has shown an efficacy of 90% [29] and 86% [35]. The efficacy reported in the present study is comparable to that recently reported in other African countries, like Ghana [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In the Democratic Republic of Congo, two studies conducted between 2003 and 2004 in Equator, South Kivu, and Katanga provinces reported paradoxical results with 85%, 93%, and 100% of ACPR, respectively [33,34]. In two studies conducted in Gabon, AS + AQ has shown an efficacy of 90% [29] and 86% [35]. The efficacy reported in the present study is comparable to that recently reported in other African countries, like Ghana [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be pointed out that this good efficacy is highly correlated with a supervised dose administration. In fact, several studies demonstrated a lower efficacy level in case of a non-supervised administration [21-23]. This drop in compliance when the association is used in daily practice (non-supervised dose) may in the long-term result in reduction of efficacy and could lead to the selection of resistant strains [21].…”
Section: Discussionmentioning
confidence: 99%
“…Until mid-August 2004, malaria attacks were treated with artesunate monotherapy [22]; thereafter, they were treated with artesunate-amodiaquine [23].…”
Section: Outcomementioning
confidence: 99%